The Securities Issued by Joint-Stock Companies: Shares and Loan Securities - Thamer Marzouq Al-Shawabkeh; Bayan Awwad Al-Ajaleen; Noor Mohammed Al-Daraweesh (Polit Journal Scientific Journal of Politics, 2022)
The study sought to explain the different aspects of the shares and the loan securities. It also outlined all the details relating to the securities. The study also clarified how the securities of the joint-stock companies were issued in terms of their scope, legal nature, and their concept, types, characteristics, and method of circulation. The study reached the most important results by working to amend some of the legislative texts to make them clearer through their expression of content, and by adding some specific texts to address some of the shortcomings in the legislative system.